ChemInform Abstract: Constraining Cyclic Peptides to Mimic Protein Structure Motifs. Issue 8 (February 2015) - Hill, Timothy A.; Shepherd, Nicholas E.; Diness, Frederik; Fairlie, David P.
Abstract Review: [172 refs.